2023
DOI: 10.1111/ger.12696
|View full text |Cite
|
Sign up to set email alerts
|

Exploring preferences of older adults for dental services: A pilot multi‐national discrete choice experiment

Abstract: ObjectivesTo pilot an exploration of older adults' future preferences using discrete choice experiments to understand who should provide dental examinations and treatment, where these services should be provided, and participants' willingness to pay and willingness to travel.BackgroundThe proportion of older adults in the general population is increasing and is recognised as a pressing public health challenge.Materials and MethodsOlder people aged 65 years and over were recruited into this study from the UK, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent research has directly investigated the preferences of older adults regarding dental care, its provision and providers in the UK, Greece, and Switzerland, and it is important to note that some of those preferences differed by country. 26 However, assumptions about patient preference for older adults are not unique to the field of dentistry. 3 A study about identifying surgical options for patients with breast cancer found that medical providers "demonstrate an age bias against older women in their recommendations of breast conservation and breast reconstruction."…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has directly investigated the preferences of older adults regarding dental care, its provision and providers in the UK, Greece, and Switzerland, and it is important to note that some of those preferences differed by country. 26 However, assumptions about patient preference for older adults are not unique to the field of dentistry. 3 A study about identifying surgical options for patients with breast cancer found that medical providers "demonstrate an age bias against older women in their recommendations of breast conservation and breast reconstruction."…”
Section: Discussionmentioning
confidence: 99%